The Place of Uzbek Music Culture in Central Asia - Dildora Abduvahobovna Djamalova (International Journal on Orange Technologies, 2022)
The article provides general information about the cultural creativity of the peoples who worked on the territory of Central Asia until the VIII th century. In addition, opinions were given on the role of factors that took place at the stages of development of the Uzbek musical culture.